Degradation of passive film on 304 stainless steel in a simulated concrete pore solution under alternating temperature condition. (September 2020) - Feng, Xingguo; Wu, Tong; Luo, Jing-li; Lu, Xiangyu
Abstract: For simulating the performance of stainless steel reinforcement under temperature change in the tropical environment, passive behavior of 304 stainless steels was studied in the pore solutions under alternating-temperature condition. The results suggested that the passive films were more severely degraded under the higher frequency or the larger amplitude of temperature alternation. Local breakdown of passive film and cracks occurred in the films as the samples experienced the low amplitude and the high amplitude of temperature alternation, respectively. Furthermore, the rupture initially started in the inner Cr2 O3 layer and then propagated into the outer iron oxides layer.